2018
DOI: 10.1136/bmjopen-2018-023366
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised controlled trial of humanoid robot-based distraction for venipuncture pain in children

Abstract: IntroductionIntravenous insertion (IVI) is a very common procedure in the emergency department (ED). IVI is often painful and stressful for both children and their families. Currently, distraction therapy is not used as a standard of care for IVI in North America. We propose that interaction with a humanoid robot may effectively distract children during IVI thereby reducing their pain and distress.Methods and analysisThis randomised controlled superiority trial will be conducted in a Canadian paediatric ED. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…The results showed that compared to the control group, the children in the intervention group did not stop crying but smiled more during vaccination. Other studies have reported that humanoid robots intervening during the procedure can distract children [ 3 ], help reduce anxiety, cope with stress, and improve behavior during the procedure [ 4 ]. Such AI-based distraction, as a non-pharmacological method, can be widely applied in the field of pediatric medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that compared to the control group, the children in the intervention group did not stop crying but smiled more during vaccination. Other studies have reported that humanoid robots intervening during the procedure can distract children [ 3 ], help reduce anxiety, cope with stress, and improve behavior during the procedure [ 4 ]. Such AI-based distraction, as a non-pharmacological method, can be widely applied in the field of pediatric medicine.…”
Section: Introductionmentioning
confidence: 99%
“…It is equipped with a camera, two microphones, beat detection, touch sensors, foot sensors, orientation sensor, infrared mouth sensor. Three articles out of the sixteen included in the review mentioned what types of sanitation the robot require between interactions with children, two reporting on Nao being wiped down [43,44] and one reporting on Huggable's fur being removed, wiped down and washed between interactions [39]. Sanitation methods are important, as the ability to sanitize the robot may determine its appropriateness to use in a hospital setting.…”
Section: Robots Usedmentioning
confidence: 99%
“…Four studies reported on using robots as distractions for children during a medical procedure. Ali et al [44] in their RCT protocol described a plan to use pre-programmed Nao robot to distract children during venipuncture procedure at a hospital. The robot will engage the child in conversation and activity and will invite the child to blow during intravenous needle insertion (IVI) to minimize the pain.…”
Section: Guided/structured Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported that humanoid robots intervening during the procedure can distract children [3], help reduce anxiety, cope with stress, and improve behavior during the procedure [4]. Such AI-based distraction, as a non-pharmacological method, can be widely applied in the eld of pediatric medicine.…”
Section: Introductionmentioning
confidence: 99%